Multisensory biofeedback: Promoting the recessive somatosensory control in operatic singing pedagogy. (April 2021) - Angelakis, E.; Andreopoulou, A.; Georgaki, A.
Highlights: Scholars, critics, and opera professionals report a decline in Lyric Singing. Multiple sciences, research the singing mechanism and performance high demands. Vocal pedagogy does not incorporate technological and scientific resources. Multisensory biofeedback tools could enhance somatosensory control and awareness. A holistic pedagogic approach is proposed using multimodal tools with biofeedback. Abstract: The quality level in Operatic Singing has been repeatedly reported as declining by a number of academic scholars, music critics, and distinguished opera professionals and teachers, during the last few decades. This narrative review attempts to combine scientific research results from Physiology, Acoustics, Psychoacoustics, Sociology, and Cognitive Sciences, in order to find possible causes for such a change and suggest applicable solutions. The opera singing profession has been widely regarded as an extremely demanding specialty, requiring high levels of cognitive awareness and muscular motor control. The stagnant empiric vocal pedagogy system in conjunction with other aspects of the modern way of life are possible factors impeding the achievement of such an elite level. Today, we have the technological resources and scientific data available, but they have not necessarily been widely used toward the development of tools for the aspiring operatic singers' training. Moreover, any such tools are usually concerned specifically with the acoustic analysis and contemporary vocal performance, but rarely factor in the kinesthetic singing properties. In this review, we suggest that Opera singers would benefit from educational strategies and specialized multi-sensory biofeedback tools that will a) promote their somatosensory control and b) heighten their awareness of their breathing, phonatory, and articulatory biomechanical functions and abilities.